Pilot Production of SARS-CoV-2 Related Proteins in Plants: A Proof of Concept for Rapid Repurposing of Indoor Farms Into Biomanufacturing Facilities - Diego-Martin, Borja; González, Beatriz; Vazquez-Vilar, Marta; Selma, Sara; Mateos-Fernández, Rubén; Gianoglio, Silvia; Fernández-del-Carmen, Asun; Orzáez, Diego (Frontiers in Plant Science, 2020)
The current CoVid-19 crisis is revealing the strengths and the weaknesses of the world´s capacity to respond to a global health crisis. A critical weakness has resulted from the excessive centralization of the current biomanufacturing capacities, a matter of great concern, if not a source of nationalistic tensions. On the positive side, scientific data and information have been shared at an unprecedented speed fuelled by the preprint phenomena, and this has considerably strengthened our ability to develop new technology-based solutions. In this work we explore how, in a context of rapid exchange of scientific information, plant biofactories can serve as a rapid and easily adaptable solution for local manufacturing of bioreagents, more specifically recombinant antibodies. For this purpose, we tested our ability to produce, in the framework of an academic lab and in a matter of weeks, milligram amounts of six different recombinant monoclonal antibodies against SARS-CoV-2 in Nicotiana benthamiana. For the design of the antibodies we took advantage, among other data sources, of the DNA sequence information made rapidly available by other groups in preprint publications. mAbs were all engineered as single-chain fragments fused to a human gamma Fc and transiently expressed using a viral vector. In parallel, we also produced the recombinant SARS-CoV-2 N protein and its Receptor Binding Domain (RBD) in planta and used them to test the binding specificity of the recombinant mAbs. Finally, for two of the antibodies we assayed a simple scale-up production protocol based on the extraction of apoplastic fluid. Our results indicate that gram amounts of anti-SARS-CoV-2 antibodies could be easily produced in little more than 6 weeks in repurposed greenhouses with little infrastructure requirements using N. benthamiana as production platform. Similar procedures could be easily deployed to produce diagnostic reagents and, eventually, could be adapted for rapid therapeutic responses.